Management of Occult Hypoperfusion Syndrome in Trauma Patients: A Narrative Review - Krishna Prasad G V (Asian Journal of Medical Research, 2020)
Occult hypoperfusion (OH) is connected with higher levels of morbidity and mortality after trauma. Occult hypoperfusion, defined as serum lactate concentration of more than 2.5 mmol / L persisting in the intensive care unit for more than 12 hours after admission. This refers to the reversible risk factor for negative results after traumatic injury. Occult hypoperfusion can be observed and patients at risk of complications should be classified other than frequently regulated metrics (blood pressure and heart rate), central venous oxygen saturation, and blood lactate levels. An elevated hospital duration of stay (LOS) and a greater incidence of postoperative difficulties are linked with OH. The focus of this review article is to assess the different approaches and methods involved in the management of OH syndrome in trauma patients. Identification of OH treatment methods can be helpful in reducing morbidity in patients with various injuries. The outcomes from this review article may prove beneficial to patients by rapid resuscitation and aggressive monitoring of OH. These management practices will severely reduce OH-associated morbidity and mortality. LOS, ICU readmission incidence and post-operative complications per patient was decreased by early treatment of OH.